Isolation and Molecular Detection of Enterococcus faecalis from Cow Milk of Anand City with Special Reference to Biofilm Production and Multiple Drug Resistance - Soni, Manasi M.; Anjaria, Pranav A.; Bhavsar, Prakrutik P.; Nayak, Jitendrakumar B.; Chaudhary, Jeetendrakumar H.; Brahmbhatt, Manoj N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to determine the drug resistance pattern and the occurrence of biofilm-producing Enterococcus faecalis from cow milk samples collected from in and around Anand city, Gujarat. A total of 100 samples were collected aseptically from the doorsteps of livestock farmers. Out of 100 samples, 73 (73%) samples were found to be positive on selective media, which was confirmed by polymerase chain reaction, which revealed that all the 73 isolates were of Enterococcus faecalis. The antibiotic sensitivity test showed that all the isolates were sensitive to ampicillin (100%) only, and resistance was observed against Trimethoprim (100%), Tigecycline (80.82%), Vancomycin (67.12%), Gentamicin (46.57%), Imipenem-cilastatin (28.76%), and Norfloxacin (10.95%). Out of all the positive isolates, 30.13% (22/73) were biofilm producers. So, it can be concluded that milk can be a possible intermediary vehicle for the spread of multidrug-resistant biofilm-producing enterococci strains to humans